Description of the last instar larva of Stenophylax espanioli Schmid 1957 (Trichoptera: Limnephilidae) from southern Iberian Peninsula with the barcode of the species and synoptic key for identification of the known Stenophylax larvae from the Iberian Peninsula - Ruiz-García, Antonio; Zamora-Muñoz, Carmen; Garzón, Andrés; Ferreras-Romero, Manuel (Zootaxa, 2018)
The larva of Stenophylax espanioli Schmid 1957 is described, illustrated, and compared with morphologically similar Limnephilidae larvae from the Iberian Peninsula. In addition, the sequence of fragments of the mtCOI gene in the barcode region of two individuals are reported and registered in the GenBank Database. Finally, a synoptic key of the known larvae of Stenophylax species from the Iberian Peninsula is given.